Boronic Acid Mediated Carbocyanation of Olefins and Vinylation of Alkyl Iodides. Issue 30 (14th June 2018) - Hara, Reina; Khiar, Chahinaz; Dange, Nitin S.; Bouillac, Pierre; Robert, Frédéric; Landais, Yannick
Abstract : Phenylboronic acid was shown to mediate the multicomponent free‐radical carbocyanation of olefins and the addition of alkyl iodides to vinylsulfones. The reaction of the boronic acid with di‐ tert ‐butyl hyponitrite generates an aryl radical, which can selectively abstract an iodine atom from an alkyl iodide to form the key carbon‐centered radical precursor. Arylboronic acids are thus considered efficient tin surrogates in this free‐radical process. Abstract : The tin‐free carbocyanation of olefins and the addition of alkyl iodides to vinylsulfones were developed by using phenylboronic acid as an aryl radical precursor and tin surrogate. The resulting aryl radical then selectively abstracted an iodine atom from the alkyl iodide to generate a radical that was employed in C–C bond forming processes.